ESBL-producing blaTEM-carrying Escherichia coli in cave bats of Lombok, West Nusa Tenggara, Indonesia - ALFIANA LAILI DWI AGUSTIN; MUSTOFA HELMI EFFENDI; WIWIEK TYASNINGSIH; ASWIN RAFIF KHAIRULLAH; HANI PLUMERIASTUTI; KATTY HENDRIANA PRICILIA RIWU; FIDI NUR AINI EKA PUJI DAMEANTI; SHEILA MARTY YANESTRIA; JOHN YEW HUAT TANG; SAIFUR REHMAN (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Agustin ALD, Effendi MH, Tyasningsih W, Khairullah AR, Plumeriastuti H, Riwu KHP, Dameanti FNAEP, Yanestria SM, Tang JYH, Rehman S. 2025. ESBL-producing blaTEM-carrying Escherichia coli in cave bats of Lombok, West Nusa Tenggara, Indonesia. Biodiversitas 26: 3701-3710. Bats are mammals known to carry Escherichia coli in their guano and inhabit diverse environments such as caves, forests, and human settlements. Even without prior antibiotic exposure, bats can harbor antimicrobial-resistant E. coli that may contaminate the environment and threaten public health. This study investigated bat species in Saung Pengembur Cave, Lombok, West Nusa Tenggara, Indonesia, carrying antibiotic-resistant E. coli. Bats were captured using mist nets from 4:00-10:00 PM, and their species identified through morphological measurements. Rectal swabs were collected aseptically, and bacterial isolation was performed using Eosin Methylene Blue Agar, followed by biochemical identification (IMViC test). Antibiotic susceptibility was assessed using the disk diffusion method, and isolates resistant to more than three antibiotic classes were screened for the blaTEM gene via PCR, followed by sequencing for phylogenetic analysis. Of 85 bats captured, 77 were Rhinolophus sp. and 8 Hipposideros diadema. Escherichia coli was isolated from 63 (74.1%) individuals, all exhibiting resistance to at least one antibiotic. Multidrug Resistance (MDR) was observed in 19% (12/63) of isolates, with 9 (75%) carrying the Extended Spectrum Beta-Lactamase (ESBL) gene blaTEM. The highest resistance rates were to azithromycin (46%), followed by tetracycline (23.8%), amoxicillin (20.6%), sulfamethoxazole/trimethoprim (19%), and ciprofloxacin (16.7%), with no resistance to cefotaxime. Phylogenetic analysis showed close relationships between bat isolates and E. coli from human and poultry sources in Southeast Asia and Australia. These findings highlight the role of bats as reservoirs for ESBL-producing E. coli, underscoring the need for One Health-based surveillance and public awareness regarding bat guano use, to mitigate environmental contamination and reduce the risk of antimicrobial resistance transmission to humans, animals, and the environment.